Advances in ceramic armor XI : a collection of papers presented at the 39th International Conference on Advanced Ceramics and Composites, January 25-30, 2015, Daytona Beach, Florida /: a collection of papers presented at the 39th International Conference on Advanced Ceramics and Composites, January 25-30, 2015, Daytona Beach, Florida. ([2016]) - Unknown
No abstract available